Studi Kualitatif Persepsi Citra Tubuh Remaja yang Kurus dan Gemuk Serta Upaya untuk Mencapai Tubuh Ideal Pada Siswi SMA Negeri 1 Kota Bogor - Pusparini, Pusparini; Refdanita, Refdanita; Maigoda, Tonny C; Briawan, Dodik (Jurnal Kesehatan, 2013)
Body image distortion has been linked with mind, emotion, sensation and strongly related tosize, and shape of individual performance. This research aimed to investigate the perception of bodyimage for adolesscent in the second grade of senior high school in SMAN 1 Bogor. A qualitative designwas used to conduct this research by using indepth interview with phenomenology approach. Six students,who were all women, consist of three students were overweight/obese and the other were lean.Allof students were interviewed regarding their perception related three domain areas which were: bodyperception,perception of current body and efforts for achieving the ideal body composition shape. Thefindingsindicated the three student who were overweigt/obese pointed out that they were happy andacceptedwith their performance but they were not better performing. The other of three student whowerelean stated that they had many perception with their body image such as: thin, was not goodlooking,andunbalancing high and weight. Almost all of the students had a similar perception abouttheirbody image whether they were overweight/obese and lean. They were not unhappy with their performance,but they had the same opinion about ideal body shape.